Flow-Through System of High Stability for the Measurement of Ion Activities in Clinical Chemistry - H.F. Osswald; R.E. Dohner; T. Meier; P.C. Meier; W. Simon (CHIMIA)
A flow-through arrangement for the potentiometric determination of ion activities using liquid membranes is presented. The system is designed for clinical application and gives a high long-term stability of the EMF measured (0.08 mV standard deviation over 24 hours) in blood serum samples. The reproducibility in the measurement of ion activities is compared to the one obtainable by other electrochemical techniques and to values observed in methods based on atomic spectroscopy.